Threonine-to-lysine ratio in laying hens: physiological parameters and organ weight - José Henrique Souza Costa; Edilson Paes Saraiva; Luana de Fátima Damasceno dos Santos; Romildo da Silva Neves; George Vieira do Nascimento; Jaciara Ribeiro Miranda; Neila Lidiany Ribeiro (Acta Scientiarum. Animal Sciences, 2022)
The objective of this study was to evaluate the effect of threonine:digestible lysine ratio in the diet on the physiological variables and weight of organs of light laying hens. Two hundred and ten 47 week-old Dekalb White laying hens were distributed in a completely randomized design, with five levels of threonine (0.507; 0.552; 0.597; 0.642 and 0.677%) and seven replicates of six birds each. The experimental period was 10 weeks, totaling 62 days and more eight days for the animals to adapt. The physiological parameters of cloacal temperature (CT), respiratory rate (RR) and average surface temperature (AST) were recorded weekly (7:00 am, 10:00 am, 1:00 pm, 4:00 pm, and 7:00 pm); after solid and water fasting, the birds were slaughtered to assess the absolute weight of the organs. The time of day influenced (p < 0.05) the physiological parameters RR and AST, and CT showed a significant effect (p < 0.05) of increasing levels of digestible threonine. The total weight of the pancreas, proventriculus and lung showed a significant effect (p < 0.05) of the increase in the levels of digestible threonine. The respiratory rate is affected by the levels of threonine in the diet. The 0.687% level promoted hypertrophy of the pancreas, proventriculus and lung, promoting more significant activity of these organs.